Informational constraints on the emergence of passing direction in the team sport of futsal - Corrêa, U. C.; Vilar, L.; Davids, K.; Renshaw, I. (European Journal of Sport Science, 2014)
This study investigated compound spatial and temporal measures of interpersonal interactions purported to constrain the emergence of affordances for passing direction in the team sport of futsal. For this purpose, attacker-defender interactions in 37 sequences of play from a futsal competition in which 24 male professional players participated (M=30.04 years, SD=4.10) were filmed and analysed using TACTO software. Relative angle data were used as measures to study coordination tendencies that emerged between players during performance. Results showed that the direction for a pass emerged from relative angles between: (1) the vector from a ball carrier to ball receiver and the vector from the ball carrier to the nearest defender (70°) (p<0.01) and (2) the vector from a ball carrier to ball receiver and the vector from the ball carrier to a ball receiver's nearest defender (31°) (p < 0.01). Furthermore, passing direction was also constrained by temporal information from the emergence of both angles, since the pass was performed to attacker-defender dyads with the highest velocities of these angles (p < 0.05). Results suggested that decisions on selecting the direction of a pass in the team sport of futsal emerged at critical values of these key compound motion measures.